Naringin Chelates Excessive Iron and Prevents the Formation of Amyloid-Beta Plaques in the Hippocampus of Iron-Overloaded Mice - Jahanshahi, Mehrdad; Khalili, Masoumeh; Margedari, Asra (Frontiers in Pharmacology, 2021)
Metal chelating agents are antioxidant agent, which they decrease the reductive potential and stabilize the oxidized metal ion form. In this study, we evaluated the naringin capacity in chelating iron and preventing amyloid-beta plaque formation in the hippocampus of iron-overloaded mice. Thirty-five NMRI male mice (8–10 weeks old) were provided. The mice were classified into five groups. Iron dextran was administrated as i.p. injection (100mg/kg/day) four times a week for four subsequent weeks. The treated groups received 30 and 60 mg/kg/day Naringin for a month. After histological processing, the brain sections stained with Perls' stain kit for iron spots, and Congo red was used to stain the brain and hippocampus for amyloid-beta plaques. 30 mg/kg/day of naringin was shown to decrease non-heme iron in an efficient manner; iron content in this group decreased to 16.83±0.57 µg/g wet weight, a quantity as low as that observed in the normal saline-receiving group. The non-heme iron content in the mice receiving 60 mg/kg/day of naringin was 20.73±0.65 µg/g wet weight. In addition, Aβ plaques number in CA1, CA3, and DG areas of the hippocampus decreased significantly following treatment with 30 or 60 mg/kg/day naringin. Naringin has a strong iron chelation capacity and is able to reduce the formation of amyloid plaques. So it can useful for neuroprotection and prevention of Alzheimer's disease.